The Unauthorized Audubon - DeLind, Laura B. (Laura Barwicke); Skeen, Anita (Book collections on Project MUSE., 2014)
In an age of experts and individualism, metrics and competition, The Unauthorized Audubon is something of an anachronism. In fact, its creators, printmaker Laura B. DeLind and poet Anita Skeen, never set out to produce a book at all when they began exchanging prints and poems, but something happened along the way. As they began to appreciate at a deeper level the skill involved in each other's work, they began to find meaning in small things-a pattern, a memory, a carefully chosen word. In his essay "Plugging into Essential Sources," Eric Booth introduces the concept of "response-ability." He